HEALTH-RELATED QUALITY OF LIFE ASSESSMENT USING SINGLE-INHALER DUAL VERSUS TRIPLE THERAPY IN CHRONIC OBSTRUCTIVE PULMONARY DISEASE PATIENTS - FATIMA, TALATH; SADAF, ANNIE FATIMA; AAMIR ALI, SYED; SIDDIQUI, JUNAID; ALI BAIG, MIRZA MISBA; AHMED, SYED MAHMOOD; FATIMA, MEHRUQ (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objectives: The study compared triple therapy (inhaled corticosteroids/long-acting beta2-agonists [LABA]/long-acting muscarinic antagonists [LAMA]) versus dual therapy [LABA/LAMA] in improving lung function and health-related quality of life (HRQoL) of patients with chronic obstructive pulmonary disease (COPD). Methods: This prospective and observational study compared 12 weeks of triple therapy (Formoterol – 6 mcg/Ciclesonide – 200 mcg/Tiotropium – 9 mcg) versus dual therapy (Formoterol – 6 mcg/Tiotropium – 9 mcg) in COPD patients. The primary objective included HRQoL as measured by improvement (decrease) from baseline in St. George respiratory questionnaire (SGRQ) score and COPD assessment test (CAT) scores. Coprimary endpoint included the change from baseline in forced expiratory volume in 1 second (FEV1). Results: After 12 weeks of treatment, triple therapy (n=30) and dual therapy (30), mean improvement (decrease) from baseline in SGRQ scores was −21.06 (95% CI, −24.92–−17.20) and −5.89571 (95% CI, −7.71–−4.07), respectively, and mean improvement (decrease) from baseline in CAT scores was −2.83 (95% CI, −3.73–−1.94] and −1.8 (95% CI, −2.25–−1.35), respectively. The mean change from baseline in FEV1% predicted was 3.09 (95% CI, 2.18–4.00) and 1.69 (95% CI, 1.43–1.97) for triple and dual therapy, respectively. For all the endpoints, the between-group mean differences were statistically significant (p<0.001). Conclusion: Triple therapy (Formoterol – 6 mcg/Ciclesonide – 200 mcg/Tiotropium – 9 mcg) can provide improvements in lung function and quality of life over dual therapy (Formoterol – 6 mcg/Tiotropium – 9 mcg) in patients with moderate to severe COPD. Future studies should focus on which drug combination of triple therapy is more effective and cost-effective than other possible triple therapy drug combinations.